The Influence of the Time and Temperature of Heat Treatment on the Allergenicity of Egg White Proteins - Shin, Meeyong; Han, Youngshin; Ahn, Kangmo (Allergy, asthma & immunology research, 2013)
The present study was performed to determine the factor, either duration or the temperature of heat treatment, exerting maximal and significant influence on the composition and allergenicity of egg white (EW) proteins. Raw EW and 4 kinds of heated EW (fried EW, boiled EW for 10 minutes, boiled EW for 30 minutes, and baked EW for 20 minutes at 170℃) were prepared, and subsequently protein extraction was carried out. The proteins were separated by SDS-PAGE, and then immunoglobulin E (IgE) immunoblots were performed with the sera of 7 egg-allergic patients. Furthermore, the antigenic activities of ovalbumin (OVA), ovomucoid (OM), and ovotransferrin (OT) in different EW samples were measured by inhibition enzyme-linked Immuno-sorbent assay (ELISA). In SDS-PAGE analysis, the intensity of the protein band at 45 kD (corresponding to OVA) decreased significantly in boiled EW (30 minutes) and baked EW, but no change was observed in the case of boiled EW for 10 minutes. In IgE immunoblots, the IgE response to 34-50 kD (OM and OVA) in boiled EW for 30 minutes decreased significantly, when compared with raw EW and other heated EWs. In inhibition ELISA, a significant decrease in the OVA antigenic activity was observed in boiled EW for 30 minutes amongst other heated EW samples. However, OM antigenic activity in all kinds of heated EW including boiled EW for 30 minutes did not reduce after heat treatment. The OT antigenic activity nearly disappeared in heated EWs except in the case of boiled EW for 10 minutes. Amongst 4 kinds of heated EWs, the boiled EW for 30 minutes showed the most significant changes both in composition and reduction in allergenicity. Our results revealed that the duration of heat treatment had more influence on the composition and allergenicity of EW proteins than the temperature.